Diet and gut microbiome of skipjack tuna (Katsuwonus pelamis) as indicators of environmental changes - Yufei Zhou; Alejandro Trujillo-González; Simon Nicol; Roger Huerlimann; Stephen D. Sarre; Dianne Gleeson (PLoS ONE, 2026)
Understanding the relationship between environmental changes and marine ecosystem dynamics is crucial, especially under the influence of climate events such as the El Niño Southern Oscillation (ENSO). The diet and gut microbiome of marine predators have the potential to efficiently, timely, and reliably indicate impacts of environmental and ecosystem changes, especially with the assistance of high-throughput sequencing (HTS) technology. This study investigated the gut content and microbiome of skipjack tuna ( Katsuwonus pelamis ) collected in the central Pacific Ocean during a transitional period of ENSO phases, shifting from a strong La Niña phase to a weak El Niño phase, aiming to evaluate the impacts of ENSO and other environmental factors on marine food webs and microbiome dynamics of skipjack tuna. While prey diversity was unaffected by ENSO events, skipjack tuna exhibited high diversity and opportunistic foraging patterns, with fish as the primary prey. In contrast, gut microbiome diversity was affected by ENSO events and Southern Oscillation Index (SOI). Five microbiome families (Fusobacteriaceae, Bacillaceae, Propionibacteriaceae, Beijerinckiaceae, and Comamonadaceae), which are associated with immune system functionality and nutritional provisioning of the host, displayed the most significant abundance changes between ENSO phases. A random forest model showed potential for ENSO phase classification based on the abundances of these five families, achieve high accuracy in internal validation, though the performance of external validation was mixed due to storage and sampling period differences. This study highlights the potential of skipjack tuna gut microbiome as indicators of rapid environmental changes, while acknowledging that the short sampling period requires longer-term validation across multiple ENSO cycles.